Pharmacokinetic profiles among obese and non-obese patients on valproate acid in Hospital Tengku Ampuan Rahimah: a retrospective evaluation / Nurul Husna Sodri - Sodri, Nurul Husna (2017)
Valproic acid (VPA) is the most commonly used antiepileptic drug (AED) in Malaysia. However, studies on pharmacokinetic profiles of VPA in obese epileptic population are limited. Thus, a retrospective analysis study was conducted to evaluate the pharmacokinetic profiles’ differences between obese and non-obese adult patients taking VPA monotherapy. The study also evaluated the relationship between the total body weight (TBW) and ideal body weight (IBW) and the VPA clearance (CL). A total of 224 samples from the routinely collected data in Hospital Tengku Ampuan Rahimah Klang a tertiary hospital were analysed, with 109 samples grouped as obese patients and 115 as non-obese. A regression analysis was also performed in order to characterize the patient’s factors which influence VPA CL .The pharmacokinetic profiles of VPA were statistically significant difference between the two groups (p < 0.05). TBW and IBW were found to have the similar strength of relationship in determining the VPA CL and dosing regimen. The regression model for VPA CL in study population included TBW (kg) and daily dose (mg/kg/day) as factors that have significant influence. The final model was as follows: CL (L/hr) = (0.005*TBW) + (0.018*daily dose) – 0.001. In conclusion, this study demonstrated significant differences in VPA pharmacokinetic profiles between obese and non-obese patients. TBW or IBW can be used in determining the dosing regimen and the estimation of VPA CL in obese patients